Microirrigation in Mulched Bed Production Systems: Irrigation Depths - Gary A. Clark; D. Z. Haman (EDIS)
Microirrigation involves the slow, controlled application of water to a crop using low pressures. Therefore precise and accurate placement of water to the crop can be achieved through proper design, installation, and management. In sandy soil vegetable production systems, tubing is placed along the plant row either on or slightly below the soil surface. In mulched bed production systems, the tubing is used to maintain desirable moisture conditions within all or most of the bed.